Formação para o uso das TDIC em cursos de licenciatura da área das ciências da natureza da Universidade Federal de Sergipe, Campus Professor Alberto Carvalho - Bezerra, Marcelo dos Santos (2022)
This study is linked to the line of research “Teacher Training in Natural Sciences” and it’s general objective was to investigate and understand the initial training of teachers in the educational courses of Natural Sciences at the Federal University of Sergipe, (FUS/ Professor Alberto Carvalho Campus), regarding the preparation for the use of Digital Information and Communication Technologies (DICT). As specific objectives, we sought to: analyze the place of DICT in the initial training of teachers, from the Pedagogical Projects of the Courses (PPC) in the area of Natural Sciences and identify the conceptions of the teacher educators from these courses, about their role in preparing for the use of DICT in the initial training of future basic education teachers. This is qualitative research of the case study type, allocated in the educational courses in Biological Sciences, Physics and Chemistry at (FUS/Professor Alberto Carvalho campus). The investigative path included document analysis, application of a questionnaire and semi-structured interviews. The organization and analysis of data occurred from the content analysis (BARDIN, 2011) and the classification of curricular components proposed by Guidotti (2016). The result of this study pointed out that the DICTs take place in the investigated degrees, in general, described in the legal and normative references, in the egress profile, in the skills and abilities to be developed by the undergraduate and in the curricular structure. Regarding the curricular structures of the investigated courses, it was observed that the approach to DICT in the curricular components presents different purposes, so they were classified into four categories: "Curricular component with a technical focus for the use of DICT", "Curricular component of specific knowledge of the area" "Curricular component specific to DICT", and "Professional curriculum component”. Even with the presence of these elements, the space occupied by DICTs in PPC is still discreet, since the number of mandatory curricular components, which seek to address DICT in teaching as a pedagogical tool, is still restricted. It was also observerd that teacher educators recognize the potential of DICT to improve the quality of teaching and learning processes. The reasons listed for this are related to the teaching and learning of abstract knowledge objects in the area of Natural Sciences. In addition, TDIC is understood as a tool to aid the development of teaching work. The data show that the initial training of teachers in the investigated courses is guided by a curriculum that addresses, explores, demonstrates and shares experiences on the use of DICT in the teacher's training process. There is a path to training that prepares future teachers in the area of Natural Sciences to use TDIC in their teaching practices. However, the teacher educators alluded to the need for investment in continuing education, restructuring of PPCs, integration of DICTs in the curriculum, access to technologies and adjustments to the campus infrastructure. It is understood that the discussions raised in the course of this dissertation highlight the importance of the contemporary debate on the initial training of teachers for the use of DICTs that will act in digital culture.